2016
DOI: 10.1108/ijem-08-2014-0111
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial management education needs in the Republic of Croatia, Poland and the United Kingdom

Abstract: Purpose – The purpose of this paper is to take the emergence of the knowledge mobilization as an opportunity to develop an understanding of needs for catching up appropriate knowledge application in SMEs in the Republic of Croatia, Poland and the UK. It draws upon the “frame mobilization” literature, which illuminates the role that acts as interpretation play in instigating, promoting and legitimating collective action with aim to provide “quality entrepreneurial education”. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In studies both from France and Croatia, considerable attention was paid to cooperation with universities. However, only two articles have been written on this topic (Dabic et al 2016, Scaringella 2016.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…In studies both from France and Croatia, considerable attention was paid to cooperation with universities. However, only two articles have been written on this topic (Dabic et al 2016, Scaringella 2016.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…Second, unlike existing research, which only focused on entrepreneurship cultivation for entrepreneurial leaders or entrepreneurs as a whole (Dabic et al, 2016; Din et al, 2016), the present study investigated the needs of entrepreneurial followers in the cultivation process. Based on the results of this empirical study, we suggested that the Chinese government should pay more attention to the cultivation of entrepreneurial followers, especially local ones, by publishing more rational and comprehensive policies that target entrepreneurial companies at the start-up stage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the temporal perspective, many scholars have researched entrepreneurship cultivation from a spatial point of view, in which the United States (Worsham and Dees, 2012; Elert et al, 2015; Guo et al, 2016) and the United Kingdom (Matlay, 2009; Henry and Treanor, 2010; Dabic et al, 2016) are frequently discussed. In addition, other developed European countries, such as France (Klapper, 2004; Kövesi, 2017), Germany (Klandt, 2004), and Sweden (Dahlstedt and Fejes, 2017) have also been targeted by existing studies.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The entrepreneurial university must undertake two tasks: it must train future entrepreneurs, persons who will start their own businesses, and foster entrepreneurial spirit in students in all subject areas-for example by fulfilling the management education needs of companies (Dabic et al 2016a). Second, it must operate in an entrepreneurial manner itself, organising business incubators, technology parks, and the like, involving students in these organisations and, through them, assisting students and graduates in the founding of businesses (Schulte 2004).…”
Section: Positioning Universities In the Notion Of Oimentioning
confidence: 99%